ANALISIS BUSINESS MODEL CANVAS PADA PT CAK WANG MACRO INDONESIA - Iswara, Ulfah Setia; Widyawati, Dini; Susanti, Susanti; Setiadevi, Shinta (Jurnal Marketing, 2024)
This research aims to conduct a Canvas business model analysis which can help companies find the most appropriate business model to use to develop their business in the future. Business development is carried out continuously by always paying attention to aspects of human resources, finance, productivity, facilities/infrastructure, and marketing. The research was conducted at PT Cak Wang Macro Indonesia. This company operates in the field of coffee processing and selling coffee drinks. PT. Cak Wang Macro Indonesia has two main units, namely Macro Coffee (Single Origin and Café Solutions) and Kopi Cak Wang (Food & Beverage). The data used for business model canvas analysis consists of financial and non-financial data obtained through interviews and observations with company management. The research results show that the company has used the canvas business model which is useful for business development towards modern SMEs. Keywords: Business Model Canvas, Business Models, MSMEs